Indoor air quality in two university sports facilities - Alves, Célia A. (2018)
In July 2012, an indoor/outdoor monitoring programme was undertaken in two university sports facilities: a fronton and a gymnasium. Comfort parameters (temperature, relative humidity, and CO2), CO and total volatile organic compounds (TVOCs) were continuously monitored. Concentrations of NO2, carbonyl compounds and individual VOCs were obtained, after passive sampling, by spectrophotometry, high-performance liquid chromatography and gas chromatography with flame ionisation detection, respectively. Low volume samplers were used to collect particulate matter (PM10). During the occupancy periods, the relative humidity values were within the comfort limits in both buildings, but frequent daytime temperatures over 30°C in the gymnasium make this indoor space rather uncomfortable. The minimum ventilation rates stipulated for acceptable indoor air quality were observed in both sports facilities. It was found that cleaning activities may have a large influence on the VOC levels. Acrolein was one of the most abundant carbonyl compounds, showing concentrations above the recommended limit. Formaldehyde was detected at levels lower than those commonly reported for other indoor environments. In the fronton, the PM10 concentrations obtained during the occupancy periods ranged between 38 and 43 μg/m3.Much higher levels, from 154 to 198 μg/m3, were registered in the gymnasium. Weekend average values lower than 20 μg/m3 were obtained in both sports facilities, which are comparable to the outdoor levels throughout the week. The high particle levels in the gym are mainly due to the climbing chalk and the constant process of resuspension.